EFFECT OF INCREASING THE V´E-V´CO2 INTERCEPT ON MINUTE VENTILATION VARIABILITY AND EXERCISE TOLERANCE IN PATIENTS WITH COPD (CIPEEX, 2026)
The relationship between minute ventilation (V´E) and carbon dioxide production (V´CO2) is a relevant marker of ventilatory efficiency during exercise. In patients with chronic obstructive pulmonary disease (COPD), the intercept of the V´E-V´CO2 curve tends to be elevated, reflecting compensatory ventilatory patterns and alterations in respiratory mechanics; however, its clinical implications and association with ventilatory variability remain poorly explored. The aim of this study was to evaluate the relationship between increased V´E-V´CO2 intercept, minute ventilation variability (vV´E), and exercise tolerance in patients with COPD. This was a retrospective study including 20 patients with COPD and 14 healthy controls who underwent incremental cardiopulmonary exercise testing on a cycle ergometer. The slope, nadir, and intercept of V´E-V´CO2 were analyzed, as well as vV´E calculated by Poincaré analysis. Patients with COPD presented significantly higher V´E-V´CO2 intercept, slope, and nadir compared with controls, associated with reduced exercise time and peak oxygen uptake. vV´E was increased in patients and correlated positively with the intercept and negatively with exercise capacity. ROC analysis showed that the intercept had greater accuracy in discriminating patients from controls compared to slope and nadir. In conclusion, the increase in V´E-V´CO2 intercept is associated with greater ventilatory variability and lower exercise tolerance in patients with COPD, suggesting it may be a clinically relevant marker of ventilatory inefficiency and a potential tool for functional stratification of these patients.
Keywords: DPOC; ventilatory efficiency; exercise; intercept VE-VCO2